Healthcare providers’ beliefs about the health effects of nicotine and electronic cigarettes - Sarahrose Jonik; Daniel Berger; Shari Hrabovsky; Jonathan Foulds; Jessica Yingst (PLoS ONE, 2026)
Background Previous research has shown that a significant proportion of healthcare providers hold inaccurate beliefs about the direct health risks of nicotine. However, the extent to which these misconceptions impact beliefs about the health effects of electronic cigarettes (e-cigarettes) remains unclear. This study examines the relationship between beliefs about nicotine and e-cigarettes among healthcare providers and trainees. Methods A questionnaire was distributed via email and printed flyers to healthcare providers and medical trainees at an academic medical center. Participants rated their beliefs about the health effects of nicotine harms on a Likert scale for 3 statements: “Nicotine is the substance that... 1) makes people want to smoke, 2) causes most of the cancer related to tobacco 3) causes most cardiovascular disease (CVD) associated with smoking.” Participants were also asked, “Compared to smoking cigarettes, would you say that electronic cigarettes are...” (less harmful, just as harmful, more harmful). Means and frequencies were tabulated, and logistic regression identified variables associated with believing e-cigarettes to be less harmful than combustible cigarettes. Results Participants (n = 598) were 75.8% female with a mean age of 36.4 years (SD = 13.3). The distribution was as follows: 38.7% (n = 232) were physicians, PAs, or NPs, 27.6% (n = 165) were students, 24.4% (n = 146) were RNs, and 9.2% (n = 55) were RTs. Although 91.5% correctly identified nicotine as the chemical that makes people want to smoke, 25.9% and 42.8% incorrectly believed nicotine is the cause of cancer and CVD associated with cigarette smoking, respectively. Only 21.4% identified e-cigarettes as less harmful than cigarettes. Those believing e-cigarettes to be less harmful than combustible cigarettes were more likely to be male (OR=2.11, 95% CI 1.32–3.37), a student (OR=1.88, 95% CI 1.20–2.94), and to disagree that nicotine is the main substance that causes cancer (OR=1.39, 95% CI 1.03–1.88) or CVD (OR=1.62, 95% CI 1.23–2.13). Conclusions Inaccurate beliefs regarding nicotine harms persist among healthcare providers and are associated with beliefs about e-cigarette harms. Targeted education on the distinct risks of nicotine, e-cigarettes, and combustible tobacco products is crucial to improving understanding and to support evidence-based counseling on harm reduction strategies.